Inspiration Mining: Intersecting Improbable Connections in a New Landscape of Cultural Reflection and Influence - Maldonado, Paulo (2020)
This article aims to present a critical reflection on the collaborative curatorship of the exhibition “Intersecting Improbable Connections”. It is a transdisciplinary exhibition covering architecture, design, arts, among other fields, and calls for non-linear productive thinking strategies. It explores the intersection of unlikely relationships to inspire memorable visits to museums, and it feeds the Inspædia platform, creating a new landscape of reflection and cultural influence. It advocates a new concept of exhibition curation that minimizes costs (because it does not involve transportation or insurance for the pieces) and is intended to help stimulate creative processes. Based on a selection of content from the participating museums’ permanent exhibitions, duly marked with QR Codes, visitors can access that content that is already available on the Inspædia platform and explore potentially endless connections, without losing contact with the physical object (and vice versa).